Intraoperative Findings of Inferior Petrosal Vein During Microvascular Decompression for Hemifacial Spasm: A Single-Surgeon Experience - Wang, Mengyang; Wang, Jiajing; Zhang, Xiuling; Chai, Songshan; Cai, Yuankun; Dai, Xuan; Yang, Bangkun; Liu, Wen; Lu, Taojunjin; Mei, Zhimin; Zheng, Zhixin; Zhou, YiXuan; et al. (Frontiers in Surgery, 2022)
Objective: This study aims to evaluate the impact of the inferior petrosal veins (IPVs) on operational exploration and to analyze related anatomic features. Methods: A total of 317 patients were retrospectively studied. Surgical outcomes and postoperative complications were analyzed, and patients were divided into two groups according to whether the IPV was sacrificed or preserved. The diameter of the IPV was also recorded during operation. Furthermore, the position where the IPV drained into the jugular bulb was recorded in each patient, and the influence of different injection points on the operation was analyzed. Results: IPVs were conclusively identified in 242/317 (76.3%) of patients, with 110/242 (45.5%) of patients categorized as “IPV sacrifice” versus 132/242 (54.5%) categorized as “IPV preservation.” IPV diameter was observed to be <0.5 mm in 58 cases (23.9%), 0.5mm - 1.0 mm (≥0.5 mm and ≤1.0 mm) in 145 cases (59.9%), and >1 mm in 39 cases (16.2%). The position of IPV drainage into the jugular bulb was at the level of the accessory nerve in 163 cases (67.3%), the level of the vagus nerve in 42 cases (17.4%), and the level of the glossopharyngeal nerve or above in 37 cases (15.3%). The diameters of IPV in the sacrifice group were mainly less than 1 mm (94.5% vs. 75%, P< 0.01), and the cases with draining points near the glossopharyngeal nerve were more than that in the preservation group (27.3% vs. 5.3%, P < 0.01). Conclusion: IPV is an obstructive structure in MVD for HFS, with considerable variations in diameters and draining points. IPV near the glossopharyngeal nerve significantly impacts surgical exposure and is often sacrificed for a better view of the operation field. Meanwhile, it is feasible to maintain IPVs with a diameter >1mm.